2012
DOI: 10.1371/journal.pone.0045741
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboids of Mycobacteria: Characterization Using an aarA Mutant of Providencia stuartii and Gene Deletion in Mycobacterium smegmatis

Abstract: BackgroundRhomboids are ubiquitous proteins with unknown roles in mycobacteria. However, bioinformatics suggested putative roles in DNA replication pathways and metabolite transport. Here, mycobacterial rhomboid-encoding genes were characterized; first, using the Providencia stuartii null-rhomboid mutant and then deleted from Mycobacterium smegmatis for additional insight in mycobacteria.Methodology/Principal FindingsUsing in silico analysis we identified in M. tuberculosis genome the genes encoding two putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…2C). Similarly, an increased sensitivity to novobiocin has also been reported for mycobacterial Rho null mutants (9). In addition, cell motility was slightly reduced in the mutant strain (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…2C). Similarly, an increased sensitivity to novobiocin has also been reported for mycobacterial Rho null mutants (9). In addition, cell motility was slightly reduced in the mutant strain (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Processing of TatA activates the translocation process, allowing the export of an unknown quorumsensing signal (8). In Mycobacteria, Rho null mutants display impaired biofilm formation and increased antibiotic sensitivity (9). Rho homologs are widely represented in archaeal genomes, and the predicted proteins contain the typical multispanning transmembrane domains (TMDs) and the amino acid residues involved in catalysis (Ser-His dyad), suggesting that they are probably functional enzymes (10).…”
mentioning
confidence: 99%
“…This gene had been annotated as a putative secreted protein, which does not indicate its involvement in drug resistance and biofilm formation. Also among our unique mannotations is Rv1337 as a rhomboid protease 74 , a far more informative annotation than that from TubercuList (possible integral membrane protein), PATRIC, RefSeq, or Mtb Network Portal (S7 Table). Also absent from these databases is the involvement of Rv1337 in ciprofloxacin and novobiocin resistance and in biofilm formation 74 , which we added as functional notes.…”
Section: Significance Of Manually Curated Gene Productsmentioning
confidence: 99%
“…Also among our unique mannotations is Rv1337 as a rhomboid protease 74 , a far more informative annotation than that from TubercuList (possible integral membrane protein), PATRIC, RefSeq, or Mtb Network Portal (S7 Table). Also absent from these databases is the involvement of Rv1337 in ciprofloxacin and novobiocin resistance and in biofilm formation 74 , which we added as functional notes. Another mannotated gene, Rv3005c, encodes an oxidoreductase responsive to oxidative stress 75 .…”
Section: Significance Of Manually Curated Gene Productsmentioning
confidence: 99%
“…In bacteria, rhomboid null mutants show phenotypes that may be related to defective cell envelope and/or cell-surface structures. In Bacillus subtilis , a mutant strain in the rhomboid homolog YqgP displayed a slight decrease in glucose uptake and a defect in cell division leading to the formation of filamentous cells (Mesak et al, 2004); Mycobacterium smegmatis rhomboid mutants showed reduced capacity for biofilm formation and increased sensitivity to antibiotics (Kateete et al, 2012). So far only TatA, a protein component of the Tat translocon in the pathogenic bacterium Providencia stuartii, has been experimentally confirmed as a rhomboid substrate (Stevenson et al, 2007).…”
Section: Membrane Proteases Implicated In the Assembly Of The Archaeamentioning
confidence: 99%